Aksesibilitas Pelayanan Kesehatan di Kepulauan (Studi di Kepulauan Kangean Kabupaten Sumenep) - Urwatul, Yunita; Muluk , M.R Khairul; Hayat , Ainul (Jurnal Ilmiah Administrasi Publik, 2025)
The purpose of this study is to describe the accessibility of health services in the Kangean Islands so that they can be evaluated for local government. Researchers analyze the accessibility using 5 (five) components, namely availability, accommodation, affordability, acceptability, and distance. This research uses a qualitative descriptive approach by analyzing the related health services in the Kangean Islands from an accessibility perspective. Data collection was carried out by interview, observastion, and documentation. Some of the sources include important sources that are considered related, namely the Head of the Sumenep District Health Office, the Head of the Health Center, the local community and several parties involved in health services in the Kangean Islands. The results showed that: the availability of health services in Kangean Island is still limited. The challenge of health services in the Kangean Islands is related to geographical conditions, which causes limitations for the community to provide health services. So far, insurance services, especially BPJS, have not covered the entire population. The provision of health services in the Kangean Islands has been carried out as much as possible, but in the end the efforts made did not meet the expectations of the people in the Kangean Islands due to the existing limitations.